THE ESSENCE AND CRIMINAL CLASSIFICATION OF SEXUAL VIOLENCE IN THE CONDITIONS OF WAR (Bulletin of criminological association of Ukraine, 2023)
The characteristic signs of sexual violence should include: violent nature, which consists in intentionally causing or threatening to cause various types of injuries to the victim against his will, interests or wishes; sexual nature, which is concentrated in the intimate perception of violent acts against the victim and the desire against her will to satisfy her own sexual desire; negative consequences in the form of a negative impact on a person's physical, spiritual, mental or psychological health. The author's own interpretation of the concept of "sexual violence" is proposed as intentional criminal acts of a sexual nature in relation to the person of the victim, which are committed against her will and violate social relations in the field of protection of physical and (or) psychological health of citizens. The purpose of such illegal influence is to satisfy one's own sexual desire or urge in an unnatural way without a physiological act. The following criteria for the forensic classification of sexual violence in wartime conditions are distinguished: by the number of participants-criminals; by the form of sexual violence (physical or so-called "biological" violence; psychological or so-called "mental" violence); by the social status of the victim (sexual violence in relation to a spouse (including close persons or family members); sexual violence in relation to a person performing an official, professional or public duty; sexual violence in relation to a woman who was known to the perpetrator to be pregnant); by the age of the victim; by the determinism of the social connection between the victims and the perpetrator (sexual violence against a familiar person of the victim; sexual violence against a stranger of the victim); according to the structure of the mechanism of criminal activity (fully structural or simple); at the place of implementation of the criminal plan; by time (short-term sexual violence; long-term sexual violence).
Keywords: sexual violence; war; forensic characteristics; psychological violence; forensic classification; physical violence